A governance framework for development and assessment of national action plans on antimicrobial resistance. Issue 11 (November 2019) - Anderson, Michael; Schulze, Kai; Cassini, Alessandro; Plachouras, Diamantis; Mossialos, Elias
Summary: Strengthening governance is an essential strategy to tackling antimicrobial resistance (AMR) at all levels: global, national, regional, and local. To date, no systematic approach to governance of national action plans on AMR exists. To address this issue, we aimed to develop the first governance framework to offer guidance for both the development and assessment of national action plans on AMR. We reviewed health system governance framework reviews to inform the basic structure of our framework, international guidance documents from WHO, the Food and Agriculture Organization, the World Organisation for Animal Health, and the European Commission, and sought the input of 25 experts from international organisations, government ministries, policy institutes, and academic institutions to develop and refine our framework. The framework consists of 18 domains with 52 indicators that are contained within three governance areas: policy design, implementation tools, and monitoring and evaluation. To consider the dynamic nature of AMR, the framework is conceptualised as a cyclical process, which is responsive to the context and allows for continuous improvement and adaptation of national action plans on AMR.